Internal Medicine Residents' Knowledge and Practice of Pulmonary Tuberculosis Diagnosis. (27th June 2018) - Chida, Natasha; Brown, Christopher; Mathad, Jyoti; Carpenter, Kelly; Nelson, George; Schechter, Marcos C; Giles, Natalie; Rebolledo, Paulina A; Ray, Susan; Fabre, Valeria; Cantillo, Diana Silva; Longworth, Sarah; et al.
Abstract: Background: Internal medicine physicians are often the first providers to encounter patients with a new diagnosis of tuberculosis. Given the public health risks of missed tuberculosis cases, assessing internal medicine residents' ability to diagnose tuberculosis is important. Methods: Internal medicine resident knowledge and practice patterns in pulmonary tuberculosis diagnosis at 7 academic hospitals were assessed utilizing (a) a 10-item validated pulmonary tuberculosis diagnosis assessment tool and (b) a retrospective chart review of 343 patients who underwent a pulmonary tuberculosis evaluation while admitted to a resident-staffed internal medicine or infectious disease service. Our primary outcomes were the mean score and percentage of correct responses per assessment tool question, and the percentage of patients who had Centers for Disease Control and Prevention–recommended tuberculosis diagnostic tests obtained. Results: Of the 886 residents who received the assessment, 541 responded, yielding a response rate of 61%. The mean score on the assessment tool (SD) was 4.4 (1.6), and the correct response rate was 57% (311/541) or less on 9 of 10 questions. On chart review, each recommended test was obtained for ≤43% (148/343) of patients, other than chest x-ray (328/343; 96%). A nucleic acid amplification test was obtained for 18% (62/343) of patients, whereas 24% (83/343) had only 1 respiratory sample obtained. Twenty patients were diagnosed with tuberculosis. Conclusions: Significant knowledge and practice gaps exist in internal medicine residents' abilities to diagnose tuberculosis. As residents represent the future providers who will be evaluating patients with possible tuberculosis, such deficiencies must be addressed.